Rotation at the crack tip and COD of mode I crack in anisotropic plate - Bhattacharya A. (My University, 2025)
Rigid body rotation is obtained at the points near crack tip of mode I crack in infinite anisotropic plate. Using Lekhnitskii's complex analysis procedure the rotation is expressed in terms of complex potentials and complex parameters of the material. A relation of crack tip rotation is obtained by incorporating the stress intensity factor and complex parameters for the known crack configuration. An equation of crack opening displacement is derived. For the case of plates made of composite materials the features of crack tip rotation and crack edge profile due to mode I loading are described. © 1993 Kluwer Academic Publishers.